Preliminary clinical activity of TP-0903 in relapsed or refractory acute myeloid leukemia with FLT3-ITD mutations - Bhatnagar, Bhavana; Buelow, Daelynn R.; Dvorak-Kornaus, Kaitlyn M.; Orwick, Shelley J.; Yoon Jeon, Jae; Talebi, Zahra; Ruppert, Amy S.; Blachly, James S.; Borate, Uma; Baker, Sharyn D. (Frontiers in Hematology, 2025)
Acute myeloid leukemia (AML) patients with FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD) experience shorter disease-free survival and high relapse rates even with FLT3 inhibitor therapy. One of the main mechanisms for loss of response is the acquisition of molecular mutations that confer drug resistance to FLT3 inhibitors. TP-0903 is an oral multi-kinase inhibitor with activity against FLT3 and several other kinases known to mediate drug resistance. Three heavily treated relapsed/refractory AML patients with FLT3-ITD were treated with TP-0903 50 mg daily, on a phase 1b/2 clinical trial, for as long as disease response or clinical benefit was observed. The dose for one patient was reduced to 37 mg daily mid-cycle after developing grade 3 nausea that improved to grade 2 within 24 h of holding doses of TP-0903. All patients achieved stable disease; however, a significant reduction in bone marrow blast percentage after one to two cycles of treatment was observed in two patients, which correlated with a decrease in FLT3-ITD allelic ratio and variant allele frequency of co-occurring mutations (e.g., NPM1 and DNMT3A). TP-0903 was feasible with no unusual toxicity signals. Additional preclinical and clinical studies are needed in order to determine the role of TP-0903 in AML.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT04518345.